Optimization of the Bugs Classification of the Ticketing System in Software Development: a Study Case - Ardhito, Danar; Girsang, Abba Suganda (CommIT (Communication and Information Technology) Journal, 2016)
Computer bug elimination is an important phase in the software development process. A ticketing system is usually used to classify the identified bug type and to assign a suitable developer. This system is handled manually and error prone. This paper proposes a new bug classification method using the fast string search algorithm. The method searches the error string and compares it to the full text. The approach is deployed to the software development process at PT. Selaras Anugerah Lestari and it results in a significant reduction in the average value of the time required to handle the bugs.